PENGARUH TOTAL QUALITY MANAGEMENT DAN QUALITY MANAGEMENT INFORMATION TERHADAP KINERJA PERUSAHAAN - OEY HANNES WIDJAYA; IAN NURPATRIA SURYAWAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
This study aimed to determine the effect of total quality management and quality management information on the firm performance which Is a company engaged in tire manufacturing. A method of data collection is done by distributing questionnaires to all employees’ quality assurance totaling 19 people. The test results suggest that there is a positive influence of total quality management and quality management information on the firm performance.